The Critical Need for Software Architecture Practices in Software Development Process - Gambo, Ishaya; Ikono, Rhoda; Iroju, Olaronke; Omodunbi, Theressa (Computer Engineering and Intelligent Systems, 2023)
Computer Engineering and Intelligent Systems, Volume 3 ,No 7,p.2-7.